2022
DOI: 10.3390/biomedicines10102477
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinases in Musculoskeletal Diseases

Abstract: Musculoskeletal disorders include rheumatoid arthritis, osteoarthritis, sarcopenia, injury, stiffness, and bone loss. The prevalence of these conditions is frequent among elderly populations with significant mobility and mortality rates. This may lead to extreme discomfort and detrimental effect on the patient’s health and socioeconomic situation. Muscles, ligaments, tendons, and soft tissue are vital for body function and movement. Matrix metalloproteinases (MMPs) are regulatory proteases involved in synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 99 publications
1
18
0
Order By: Relevance
“…Metalloendopeptidase includes a disintegrin and metalloprotease (ADAM) and matrix metalloproteinases (MMPs), in which MMPs partici in the process of OA through synthesis, degradation, and remodelpateing of extracellular matrix components [32]. Our discoveries are consistent with these studies.…”
Section: Discussionsupporting
confidence: 86%
“…Metalloendopeptidase includes a disintegrin and metalloprotease (ADAM) and matrix metalloproteinases (MMPs), in which MMPs partici in the process of OA through synthesis, degradation, and remodelpateing of extracellular matrix components [32]. Our discoveries are consistent with these studies.…”
Section: Discussionsupporting
confidence: 86%
“…[72,73] Meanwhile, the another hallmark of the disease is the change in physical microenvironment matrix, especially in ECM stiffness characterized by osteophyte formation. [21,74,75] This is due to the composition changes of the cartilage matrix, characterized by a loss of proteoglycan, [76] changes in collagen type deposition, a scattered distribution of prototypic collagen fibrils [77] and fibrosis of the collagen network. [78,79] The correlation between ECM stiffness and composition has been well discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of epidemiological studies have shown that the consumption of tea/green tea reduces various types of cancer [ 7 ]. For example, in a pooled analysis of eight population-based cohort studies, females who consumed green tea showed a decreased risk of total cancer mortality: pooled hazard ratios (HR) = 0.89 (95% confidence intervals (CI) = 0.83–0.96) for the consumption of 1–2 cups/day and HR = 0.91 (95% CI = 0.85–0.98) for the 3–4 cups/day [ 10 ].…”
Section: Anticancer Effects Of Egcgmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are zinc-dependent metalloproteases capable of degrading extracellular matrix proteins [ 6 , 7 , 8 ]. In humans, at least 23 different MMPs have been found [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation